2018
DOI: 10.1177/1548051818806290
|View full text |Cite
|
Sign up to set email alerts
|

Empathetic Leadership: How Leader Emotional Support and Understanding Influences Follower Performance

Abstract: This article presents a theory of empathetic leadership and its initial test. Empathetic leadership provides a model of how leader understanding and support improves follower behaviors and affective states. For this article, we explored the link between empathetic leadership and follower performance. Specifically, we tested the causal processes by which empathetic language influences follower performance. These processes include follower job satisfaction and innovation. Findings support model hypotheses and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(143 citation statements)
references
References 147 publications
(178 reference statements)
8
115
0
5
Order By: Relevance
“…Indeed, prior work has suggested that individuals with lower need for cognition are more likely to focus on extraneous, peripheral information during interactions (e.g., Cacioppo et al., 1986; Ras et al., 2015; Ting, 2012), which suggests that leaders with lower need for cognition may be more readily distracted by the information that is being conveyed and its meaning when they are the targets of venting receipt. Thus, although organizational scholars and practitioners have described listening and providing support as a valued and necessary daily leader activity (e.g., Drucker, 2004; Kock, Mayfield, Mayfield, Sexton, & De La Garza, 2019; Lloyd, Boer, Keller, & Voelpel, 2015), our findings suggest that doing so can be challenging for certain leaders.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, prior work has suggested that individuals with lower need for cognition are more likely to focus on extraneous, peripheral information during interactions (e.g., Cacioppo et al., 1986; Ras et al., 2015; Ting, 2012), which suggests that leaders with lower need for cognition may be more readily distracted by the information that is being conveyed and its meaning when they are the targets of venting receipt. Thus, although organizational scholars and practitioners have described listening and providing support as a valued and necessary daily leader activity (e.g., Drucker, 2004; Kock, Mayfield, Mayfield, Sexton, & De La Garza, 2019; Lloyd, Boer, Keller, & Voelpel, 2015), our findings suggest that doing so can be challenging for certain leaders.…”
Section: Discussionmentioning
confidence: 65%
“…For example, a study of 257 respondents from the southwest United States confirmed that empathetic leadership has a positive relationship with employees' job satisfaction. Further, empathic leadership unlike laissez-faire leadership promotes innovation and employee performance (Kock, Mayfield, Mayfield, Sexton, & De La Garza, 2019). Similarly, Skinner and Spurgeon (2005) studied Australian managers to confirm a relationship between empathy and transformational leadership styles.…”
Section: Leadership Styles and Workplace Bullyingmentioning
confidence: 99%
“…improvements in terms of social distancing, hygiene, and pandemic preparedness; or conversely, may resist changes that render work environments less comfortable, ergonomic, or convivial. Methods to support the psychological resilience of employees can be critical, such as internal counseling services and support groups, team-building and consultation activities, regular demonstration of management's attentiveness to staff concerns and welfare, and leadership that evidences empathy and supportiveness [Kock et al, 2018]. Again, specialist KIBS provide advice in many of these areas.…”
Section: Relating To New Demands Concerningmentioning
confidence: 99%